Aplicação da Neuroarquitetura em Centro de Integração e Apoio para crianças com TEA (Transtorno do Espectro Autista) - Nobre, Karen Kelen Silva (Brasil, 2022)
The present Course Conclusion Work aims to research and gather the necessary concepts that support and justify the proposal to implement the project of an Integration and Support Center for Children with Autism Spectrum Disorder in Manaus, through the application of Neuroarchitecture and the your way of designing. The purpose of such implementation is given by the constant need for spaces for the autistic public with the necessary support for the development of their therapies and activities for social and motor growth. Therefore, the present work proposes the use of neuroscience applied to architecture in order to develop an architectural project where the sensory needs of autistic individuals are taken into account in the design act, in order to create spaces that support the full development of these children.